"Deconstruimos la educación patriarcal desde el lente feminista": construyendo una educación liberadora en clave antirracista, feminista y decolonial. - SANTIAGO ORTIZ, AURORA (Centro Journal)
In this article, the author addresses the need to implement a gender perspective education in Puerto Rico. The importance of dismantling oppressive and colonial systems through (re)education that promotes gender equality and social justice is highlighted. The text presents a summary of an interdisciplinary research course that took place at the University of Puerto Rico-Cayey, focused on social transformation through the combination of action and reflection. The influence of Paulo Freire's pedagogy of liberation and decolonial feminist theory in the construction of a decolonial feminist pedagogy is mentioned. Additionally, the importance of solidarity and equitable participation in building relationships based on social justice is emphasized. The article also discusses the lack of a gender perspective in public education in Puerto Rico and the conservative resistance to the implementation of gender perspective education. The importance of decolonizing the educational system and working to reduce oppression caused by the capitalist system is mentioned. The text highlights the role of public universities in critical thinking and the formation of individuals committed to socioeconomic development and community life.